HIV be safe not sorry (Bangkok UNDP South East Asia HIV and Development Programme, 2004)
This training programme aims to raise the level of awareness of HIV/AIDS among seafarers in the Asia, Pacific region. This in turn will help prevent the spread of HIV infection in this region. The programme has a built in assessment to test the seafarer's awareness of HIV/AIDS. A project jointly developed by United Nations Economic and Social Commission for Asia and the Pacific, UNDP (United Nations Development Programme), UNAIDS (Joint United Nations Programme on HIV/AIDS), Singapore Maritime Academy.
System requirements: Windows 9X, NT, 2000 and XP; Pentium II 266 or above; 300 MB hard disk space (minimum); 128 MB RAM; 800 x 600 monitor resolution with minimum 16K color display; 16 MB video RAM; 16 bit sound blaster or compatible; 24X CD-ROM speed; keyboard and mouse; Multimedia speakers and headphones; Printer